Seed dispersers shape the pulp nutrients of fleshy-fruited plants - Lei, B; Cui, J; Newman, C; Buesching, CD; Xie, Z; Macdonald, DW; Zhou, Y (The Royal Society, 2021)
The dispersal-syndrome hypothesis posits that fruit traits are a product of selection by frugivores. Although criticized as adaptationist, recent studies have suggested that traits such as fruit or seed size, colour and odour exhibit signatures that imply selection by animal mutualists. These traits imply nutritional rewards (e.g. lipid, carbohydrate), attracting frugivores; however, this remains incompletely resolved. Here, we investigated whether fruit nutrients (lipid, sugar, protein, vitamin C, water content) moderate the co-adaptation of key disperser-group mutualisms. Multivariate techniques revealed that fruit nutrients assembled non-randomly and grouped according to key dispersal modes. Bird-dispersed fruits were richer in lipids than mammal-dispersed fruits. Mixed-dispersed fruits had significantly higher vitamin C than did mammal- or bird-dispersed fruits separately. Sugar and water content were consistently high irrespective of dispersal modes, suggesting that these traits appeal to both avian and mammalian frugivores to match high-energy requirements. Similarly, protein content was low irrespective of dispersal modes, corroborating that birds and mammals avoid protein-rich fruits, which are often associated with toxic levels of nitrogenous secondary compounds. Our results provide substantial over-arching evidence that seed disperser assemblages co-exert fundamental selection pressures on fruit nutrient trait adaptation, with broad implications for structuring fruit-frugivore mutualism and maintaining fruit trait diversity.